Identification of two sweet and sour acerola (Malpighia glabra L.) varieties by morphology and protein electrophoresis - Thanh Tuyen, Tran Thi; Toan, Nguyen Bao (Academia Journal of Biology, 2012)
Acerola (Malpighia glabra L.) was one of the fruit trees cultivated popularly in some provinces of Mekong Delta. The largest cultivated areas of these trees were Go Cong districts (West and East Go Cong), Tien Giang province. Nowadays, there were two sour and sweet acerola varieties:cultivated. Identification of these two varieties through morphology was very difficult and easy to mistake. Protein electrophoresis was a good tool to identify varietties. This research aimed to identify two sour and sweet acerola varieties based on morphology and protein electrophoresis. Acerola samples used in research were collected on two kinds of soil: sandy silt and sandy soils. Protein electrophoresis were analysed according to Hames (1998). Research results showed that there were differeces at some morphological characteristics such as flower and fruit diameters. However, morphological characteristics were often influenced easily by environmental impacts. While flower was not influenced. Flower diagram analysis showed that both varieties were very similar. Thus these morphological characteristics have not yet enough information to distinguish two varieties.  Results of protein electrophoresis showed that there were quite differences between two sour and sweet acerola varieties. Differences were detected at bands which molecular weights were 51.89 kDa, 31.08 kDa and 28.06 kDa.